Mean of Modeling of the Informative System of Monitoring of Education is the Class Diagram UML (Journal of Information Technologies in Education (ITE), 2008)
In the article the features of functioning of the informational-analytical system for multilevel monitoring of education are considered. The described class diagram UML for the design of the informational-analytical system for multilevel monitoring of higher educational establishment. This diagram describes the static type of the system in relation to processes, represents properties of objects and subjects, their co-operation. Also allows to analyzed the great number of the states of elements of the system.